THE LEGAL STATUS OF TRADE UNIONS AND POTENTIAL GROUNDS ON WHICH THEY MAY INCUR LIABILITY - ME Manamela (Obiter, 2024)
Employees exercise their right to freedom of association by forming or joining trade unions. It is not required that a trade union be registered to function as such. However, under the Labour Relations Act (LRA), there are a number of benefits available to registered trade unions. A registered trade union acquires the status of a body corporate with rights and duties. However, it functions through natural persons, and those who represent it may not be held liable if they act in line with the union’s constitution and within their authority. This article is aimed at considering the legal status of trade unions in South Africa and in the United Kingdom (UK) respectively. It further considers different circumstances under which a trade union may incur liability, including instances where there is non-compliance with the union’s constitution, a breach of contract or delict, or a discrimination claim.